Sequence stratigraphic analysis and hydrocarbon prospectivity of AMO Field, deep offshore Niger Delta, Nigeria - Adeniyi Amodu (KeAi Communications Co., Ltd., 2022)
An integrated interpretation of processed 3D seismic data, a suite of well logs, biostratigraphic data and core photographs of AMO Field, deep offshore Niger Delta, is carried out for the sequence stratigraphic analysis of strata penetrated by wells. Lithologic and key stratigraphic surfaces, that is, the maximum flooding surfaces (MFSs) and sequence boundaries (SBs), are identified based on bioevents and log motifs. Biostratigraphic data help the delineation of MFSs and SBs, as well as dating, determination of depositional environment and paleobathymetry. The sequence stratigraphic study reveals seven MFSs (of 13.0 Ma, 11.0 Ma, 9.5 Ma, 7.4 Ma, 5.8 Ma, 5.0 Ma and 2.7 Ma) and six SBs (of 12.1 Ma, 10.3 Ma, 8.5 Ma, 6.3 Ma, 5.5 Ma and 4.2 Ma). The key stratigraphic surfaces identified involve three depositional sequences characterized by lowstand, transgressive and highstand system tracts respectively. The studied section is deposited in a deepwater environment ranging from Lower to Upper Bathyal and can be dated back to the Middle Miocene - Middle Pliocene in age. Seven faults and two horizons (corresponding to reservoir units) are identified and mapped across the seismic data volume to establish a continuity of the reservoir to areas lacking well control. The established sequence stratigraphic framework displays successions of sediments (system tracts) where the reservoir sand units of the lowstand and highstand system tracts are of hydrocarbon prospective units in the field.